More than handmaids: Nursing, labor activism and feminism. Issue 4 (7th February 2022) - Lingel, Jessa; Clark-Parsons, Rosemary; Branciforte, Kim
Abstract: In the United States, the nursing profession has been dominated by women, who constitute nearly 90% of the workforce. The profession's popularity among women has consequences for gendered assumptions about labor: unions represent a key path for demanding equitable working conditions, yet the gendered framing of nursing has undermined efforts at building a labor movement within the profession. We offer two contributions with this paper: documenting the working lives of women nurses at a pediatric hospital in Oakland, CA, and unpacking the interrelated tensions between nursing, union work, and feminism. Drawing on interviews with 10 women nurses at Children's Hospital Oakland, we analyze the complex negotiations between gender and feminism that emerge in the everyday lives of union nurses. We use the concept of feminist agency as an organizing principle for understanding the disconnects between nurses and feminist discourse, and the affordances of labor activism for gaining workplace equity and mobilizing broader commitments to health justice.